Preoperative Computed Tomographic Angiogram for Deep Inferior Epigastric Artery Perforator Flap for Breast Reconstruction: The Imaging Mapping Era - Masia, Jaume; Navarro, Carmen; Clavero, Juan A.; Alomar, Xavier (IntechOpen, 2012)
None